(untitled) (Journal of Bangladesh Academy of Sciences, 2011)
The spinel ferrite of Ni0.20Cu0.30Zn0.50Fe2O4 was studied at room temperature using X-ray diffraction pattern prepared by auto combustion technique. The analysis of the XRD patterns showed that the sample has a single phase cubic spinel structure. The bulk density, average grain size and initial permeability increase with increasing sintering temperature up to a optimum temperature. Beyond that temperature all those properties decreases. The value of relative quality factor decreases with increasing sintering temperature. The DC magnetization measurement showed that at room temperature the sample is in ferrimagnetic state. The number of Bohr magneton, n(?B), Néel temperature, TN, and the field at which saturation occurs were also calculated and possible explanation for the observed characteristics of microstructure, initial permeability, DC magnetization, and Néel temperature of the studied sample are presented. DOI: http://dx.doi.org/10.3329/jbas.v35i1.7972 Journal of Bangladesh Academy of Sciences, Vol.35, No.1, 67-75, 2011